Physical impact indicators for mountain trails at Gunung Tahan Trail, Malaysia - Yaakob, Sam Shor Nahar (2019)
Mountain trekking in Malaysia has been growing in popularity as evident from the increasing number of trekkers to popular mountain tops in the country. Mountain trails are usually the most practical access to these mountain tops. These trails are usually subjected to various physical impacts as they are extensively used by the trekkers. Thus, indicators are needed if physical impacts at the mountain trails are to be managed. This study was conducted to determine suitable physical impact indicators for mountain trails in Malaysia. The Gunung Tahan Trail, which leads up to Gunung Tahan summit in Taman Negara National Park, serves as the study site. A self-administered questionnaire was used to obtain the data for the study. An on-site and off-site survey was used to recruit 336 respondents from Gunung Tahan climbers. In addition, an expert panel consisting of 24 individuals in resource conservation were also included as respondents. The respondents were asked to rate the suitability of 27 selected physical impact indicators based on a 5-point Likert scale ranging from 1 (most unsuitable indicator) to 5 (most suitable indicator). In addition, other variables such as respondent’s demographic, motives and previous mountain climbing experience were also gathered. General agreement on the most suitable indicators were determined by subjecting the data to a number of statistical tests of significance; independent t-test, multivariate analysis of variance (MANOVA) and multivariate analysis of covariance (MANCOVA).The results of the analysis showed that sixteen physical impact indicators were suitable for Gunung Tahan Trail. This covers impacts on soil - depth of trail, width of trail, presence of muddy area, presence of wet surfaces, presence of gully, bare surface area, soil compaction, problem area condition, soil drainage, loss of organic matter, problem area coverage (size); impacts on vegetation - root exposure condition, leaned trees; and physical impacts by human - presence of vandalism and presence of multiple trails. The physical impacts on soil are of the most concerned by the respondents based on the selected number and mean scores of these indicators in comparison to vegetation and human impact indicators. These indicators would be useful in managing the trail resources and mountain trekking experiences. Furthermore, the indicators can be applied to determine the carrying capacity and other visitor management strategies for the mountain trails in Malaysia.